Propuesta de mejora para el proceso de exportación de ropa a Miami, para la empresa Diseños Claudia Soto. - Moreno Cortez, Rodrigo Andrés (Universidad Antonio Nariño, 2022)
Proposal for Improvement in the Management of Exportation of Women's Clothing from Colombia to Miami / Florida for the Claudia Sotto Designs Company, is an internship document carried out within the framework of the international trade career in order to contribute with a export improvement plan for the aforementioned company.